The Palgrave Concise Historical Atlas of Eastern Europe - Hupchick, D. author. aut Link
VIII, 130 p.
Keywords: The Palgrave Concise Historical Atlas of Eastern Europe is a lucid and authoritative guide to a full understanding of the complicated history of Eastern Europe. Addressing the need for a comprehensive map collection for reference and classroom use, this volume includes fifty two two-colour full page maps which are each accompanied by a facing page of explanatory text to provide a useful aid in physical geography and in an area's political development over time. The maps illustrate key moments in East European history from the Middle Ages to the present, in a way that is immediate and comprehensible. Lecturers and students will find it to be an indispensable and affordable classroom and reference tool, and general readers will enjoy it for its clarity and wealth of information.